2023
DOI: 10.3390/healthcare11172436
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating Changes in Trauma Epidemiology during the COVID-19 Lockdown: Insights and Implications for Public Health and Disaster Preparedness

Mariusz Jojczuk,
Jakub Pawlikowski,
Piotr Kamiński
et al.

Abstract: The COVID-19 pandemic demanded changes in healthcare systems worldwide. The lockdown brought about difficulties in healthcare access. However, trauma still required further attention considering its modifications. The presented study aims to investigate the variances in epidemiological patterns of trauma during the lockdown and the previous year, with a view to better understand the modifications in healthcare provision. The authors analyzed data from the first lockdown in 2020 (12 March–30 May) and the same p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…A significant increase in the age of patients who suffered from an injury during the pandemic may be related to the restrictions introduced, including those on movement and ordering social distance, which mainly affected people of school and working age. A study involving patients hospitalised for injuries in Lubelskie voivodeship in Poland indicates that the median age of patients with injuries increased from 40 years in the pre-pandemic period to 46 years during the pandemic [ 27 ]. A Dutch study also observed that during the pandemic, the mean age of patients with injuries was higher and amounted to 48 years as compared to 42 years in 2019 and 43 years in 2018 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A significant increase in the age of patients who suffered from an injury during the pandemic may be related to the restrictions introduced, including those on movement and ordering social distance, which mainly affected people of school and working age. A study involving patients hospitalised for injuries in Lubelskie voivodeship in Poland indicates that the median age of patients with injuries increased from 40 years in the pre-pandemic period to 46 years during the pandemic [ 27 ]. A Dutch study also observed that during the pandemic, the mean age of patients with injuries was higher and amounted to 48 years as compared to 42 years in 2019 and 43 years in 2018 [ 26 ].…”
Section: Discussionmentioning
confidence: 99%
“…These restrictions, as mentioned earlier, reduce the risk of injuries, especially in younger patients who are characterised by greater mobility and a tendency to engage in risky activities as compared to the elderly. Jojczuk et al report that in 2020, compared to 2019, the proportion of patients with injuries admitted to hospitals in Lubelskie voivodeship (Poland) decreased in the age groups of 1–17 years (to 10.4% from 16.3%) and 18–45 years (to 39.5% from 40.4%), whereas it increased in the age ranges of 46–65 years (to 25.7% from 23.8%) and over 65 years (to 24.4% from 19.5%) [ 27 ]. In 2020, compared to the pre-pandemic period, in the Children’s Hospital in Montreal, Canada, a reduction in the number of injury-related visits to the emergency department was observed in all age groups, with the smallest decrease noted for children aged 2 to 5 years (35%), and the largest decrease for the 12- to 17-year-old group (83%) [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Marincovitz et al, similar to the results of our study, revealed that injuries at home were more common during the lockdown in England [ 12 ]. Jojczuk et al also emphasized in the data they recorded in Poland that traumas at home were more common during the lockdown periods [ 13 ]. It is understood that major traumas such as traffic accidents decreased proportionally because of going out less frequently and taking fewer vehicle trips, and that less severe traumas such as falling from one’s own height on the ground were higher in percentage during lockdown periods.…”
Section: Discussionmentioning
confidence: 99%
“…Gradually, times of normalization began to occur [ 11 ]. During lockdown periods, there were changes in trauma mechanisms, as well as some other factors, for the elderly [ 12 , 13 ]. These lockdowns targeting the elderly population, together with the infectious disease aspect of the pandemic, may have brought about a change in the incidence and mechanisms of trauma, and accordingly, in the experiences of the patients in Turkey.…”
Section: Introductionmentioning
confidence: 99%